2022
DOI: 10.1111/jcal.12655
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Taiwanese learning effects of Shaking‐On and Kahoot!

Abstract: Background: Many gamification applications (apps) have been designed to motivate students to learn particular content. Based on the brain activation approach, the present study adapted an app, named Shaking-On, which requires students to shake their mobile devices to send their answers to multiple-choice questions to the teacher. Students then learn from their performance.Objectives: To understand how this approach can stimulate participants' emotions when achieving their learning goals, the present study comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 79 publications
(118 reference statements)
0
1
0
Order By: Relevance
“…It is crucial in assessing ChatGPT's potential as an instructional tool, especially in terms of time efficiency and its impact on learning (Durik et al,2015;Zwain,2019). The effectiveness of instructional tools directly affects students' confidence and motivation (Ain, Kaur, & Waheed, 2016;Hong et al, 2022). If learners don't see a tool as beneficial for their learning, it can diminish their enthusiasm (Dajani & Hegleh, 2019).…”
Section: Learning Valuementioning
confidence: 99%
“…It is crucial in assessing ChatGPT's potential as an instructional tool, especially in terms of time efficiency and its impact on learning (Durik et al,2015;Zwain,2019). The effectiveness of instructional tools directly affects students' confidence and motivation (Ain, Kaur, & Waheed, 2016;Hong et al, 2022). If learners don't see a tool as beneficial for their learning, it can diminish their enthusiasm (Dajani & Hegleh, 2019).…”
Section: Learning Valuementioning
confidence: 99%
“…They found that GBLL could promote K‐12 students' peer interactions and reduce achievement gaps between the disadvantaged and advantaged students. Besides language proficiency, Hong, Tai, et al (2022) explored the influence of question‐based gamification applications on K‐12 students' emotional perceptions, and obtained improved gameplay interest, flow experience and perceived learning value. Hsu and Liang (2021) also asserted that digital board games could enhance K‐12 students' vocabulary sizes, foster critical thinking and computational thinking skills, and reduce anxiety levels.…”
Section: Introductionmentioning
confidence: 99%